Foreign earnings management of US multinational companies: The role of decision rights - Huang, Jing (Journal of International Business Studies, 2018)
US multinational corporations (MNCs) need to allocate decision rights between parent companies and subsidiaries to manage global operations. This article examines how the allocation of decision rights affects foreign earnings management of MNCs. I find that the extent of foreign earnings management increases when parents retain centralized decision rights. But internal cross-border frictions, between parents and their foreign subsidiaries, and the external local legal environment in which foreign subsidiaries operate can mitigate foreign earnings management despite parents having centralized decision rights. This study provides evidence on how the decision structures of MNCs affect where earnings are managed.